2013
DOI: 10.1159/000349995
|View full text |Cite
|
Sign up to set email alerts
|

Unbound Free Fatty Acids from Preterm Infants Treated with Intralipid Decouples Unbound from Total Bilirubin Potentially Making Phototherapy Ineffective

Abstract: Extremely low birth weight (ELBW; <1,000 g) infantshave poor outcomes, often compromised by bilirubin neurotoxicity. We measured unbound bilirubin (Bf) and unbound free fatty acid (FFAu) levels in 5 ELBW infants in a trial examining the effects of pharmacologic ductal closure on infants treated with Intralipid infusion (3 g/kg/day). The levels for all infants (mean ± SD) were: total serum bilirubin (TSB) 4.6 ± 1.7 mg/dl, FFAu 376 ± 496 nM, and Bf 42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
(35 reference statements)
1
18
0
Order By: Relevance
“…(29) Our own previous study suggested that increases in FFAu and Bf can reach extreme and toxic levels, and that under such conditions phototherapy cannot reduce Bf sufficiently. (15) This investigation was not aimed at documenting the short or long-term toxicity of elevated Bf levels, thus auditory brainstem responses in the infants were not collected. (6) The standard of care in our neonatal intensive care unit is a hearing test by an automated auditory brainstem response test that provides only pass/fail data and infants who fail this screen are referred to the audiology program where the work-up may include a diagnostic auditory brainstem evoked response test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(29) Our own previous study suggested that increases in FFAu and Bf can reach extreme and toxic levels, and that under such conditions phototherapy cannot reduce Bf sufficiently. (15) This investigation was not aimed at documenting the short or long-term toxicity of elevated Bf levels, thus auditory brainstem responses in the infants were not collected. (6) The standard of care in our neonatal intensive care unit is a hearing test by an automated auditory brainstem response test that provides only pass/fail data and infants who fail this screen are referred to the audiology program where the work-up may include a diagnostic auditory brainstem evoked response test.…”
Section: Discussionmentioning
confidence: 99%
“…The Bf probe (BL22P1B11-Rh) binds unconjugated bilirubin with high affinity (Kd=16 nM) but is poorly sensitive to FFA (Kd>3000 nM), conjugated bilirubin (Kd>300 nM), bilirubin photoisomers, bilirubin oxidation products, ibuprofen and indomethacin (17). FFAu concentrations were determined using the ADIFAB2 probe (15, 18). Fluorescence was assessed at two emission wavelengths: 457 and 550 nm for the FFAu probe and 525 and 580 nm for the Bf probe (excitation = 375 nm for both).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter competes with the bilirubin binding sites of albumin, resulting in a higher unbound or free bilirubin (Bf). Hegyi et al recently showed that increasing doses of IL administration in VLBW infants is associated with increasing levels of unbound free fatty acid (FFAu) as well as Bf (4,5). Amin et al have previously shown similar results (6).…”
Section: Introductionmentioning
confidence: 96%
“…Hegyi et al. recently showed that increasing doses of IL administration in VLBW infants is associated with increasing levels of unbound free fatty acid (FFAu) as well as Bf . Amin et al.…”
Section: Introductionmentioning
confidence: 99%